2003
DOI: 10.1051/0004-6361:20021730
|View full text |Cite
|
Sign up to set email alerts
|

A high-precision null result in the search for rapid oscillations in HD 965

Abstract: Abstract. HD 965 is a strongly magnetic peculiar A star with clear Zeeman splitting in its spectral lines, a rotation period greater than 2 yr, H-line core-wing anomaly, and strongly negative Strömgren δc 1 and δm 1 indices. All of these characteristics are typical of the rapidly oscillating Ap stars, and it has been suggested that HD 965 should be one. We have tested this star for photometric variability under excellent conditions with low scintillation noise using the 2-m TBL for 2.7 hr at Pic du Midi Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…For these three stars no rapid photometric variability was found by Martinez & Kurtz (1994). Another example of a star with significant cerium lines and no detected pulsation is HD 965 (Kurtz, Dolez & Chevreton 2003; Elkin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For these three stars no rapid photometric variability was found by Martinez & Kurtz (1994). Another example of a star with significant cerium lines and no detected pulsation is HD 965 (Kurtz, Dolez & Chevreton 2003; Elkin et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The rotation period of the star is unknown, but appears to be more than five years. The long rotation period is also a possible reason why rapid photometric variations were not found by Kurtz et al (2003a) who observed one year prior to our observations.…”
Section: Discussionmentioning
confidence: 58%
“…Kurtz et al (2003a) found an upper limit of 0.2 mmag to any photometric pulsation in the frequency range of the roAp stars.…”
Section: Introductionmentioning
confidence: 88%
“…The reason is that according to the oblique rotator model, the amplitude of the oscillation is higher near maximum of the rotational modulation and may become zero at other phases (Kurtz 1990). Therefore, Kurtz et al (2003a) stated that further observations of this star over a few years are required to substantiate its status as an noAp star. Here we report observations of the Ap star e UMa, whose rotation period is short enough to avoid this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Kurtz et al (2003a) observed the Ap star HD 965 over 2.7 hr using a 2 m telescope and put an upper limit of 0.2 mmag or ∼200 parts per million (ppm) on the amplitude of oscillations in the B band. This is the lowest limit for pulsation in an noAp star in the literature.…”
Section: Introductionmentioning
confidence: 99%